On the crystalline basement and the basal part of the Pre-Cambrian Eleonore Bay Group in the southwestern part of Scoresby Sund - Wenk, Eduard (Meddelelser om Grønland, 1961)
Explorations carried out in July and August 1958 in the lake districts between the innermost parts of Vestfjord and Gaasefjord (southwest corner of Scoresby Sund) ascertained the existence of an angular unconformity of sub-Groenlandian age. The paper deals with the general geology of that area which has been laid down in a geologic map and a section. It describes the crystalline basement of pre-Groenlandian age ("Archaean"), its autochthonous to parautochthonous Groenlandian sedimentary cover, the Caledonian crystalline rocks thrust westwards over the basement and its sediments, and touches on the Tertiary plateau basalts overlying all the other formations as horizontal sheets. The psephitic series above the unconformity, representing the base of the Eleonore Bay Group, is discussed in more detail. From the character of deposition, the wide range of grain-size and roundness, the lack of alteration of the minerals, the microscopic fabric and the chemical composition of the clay matrix, and the varve structure of the clay beds, it is deduced that this series represents glacial sediments deposited in water. The limestones and the thick pelitic series above the psephitic beds make it possible to think of a correlation with the type sections of the Petermann region and thus permit us to conclude that the sediments concerned represent the basal part of the Eleonore Bay Group. Accordingly this group starts and ends with glacial deposits.